Impact of anthropometric characteristics and physical performance components on serve velocity in elite male junior tennis players - Fett, J.; Ulbricht, A.; Ferrauti, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In tennis, modern game has evolved from a primary technical to the current explosive sport becoming increasingly dynamic and faster based on strength, speed and power with higher stroke and serve velocities leading the service game to a key factor of game success. Consequently, velocity production is an obvious prerequisite to proficient tennis serve performance. However, there is no consent whether physical and anthropometric attributes are good predictors of service speed. Therefore, the aim of the study was to examine the impact of physical performance characteristics and anthropometric variables on serve performance (i.e. velocity). Methods: 625 male junior squad players of the German Tennis Federation (13.7±1.9yrs, 165.4±13.4cm, 53.0±13.7kg) participated in this study. All subjects, matched into 2yrs age categories (U12,U14,U16,U18), performed the standardized German Physical Condition Tennis Test including body height [BH], body mass [BM], sitting height [SH], arm span [AS], serve velocity [SV], medicine ball throw [MBT] overhead [OH], forehand [FH], backhand [BH], hand grip strength [GS], countermovement jump [CMJ], horizontal jumps [HJ], 20m sprint [S], and tennisspecific endurance [E] [1]. Partial correlation as well as multiple regression analysis was used to determine the relation and contribution of anthropometric and physical performance to service speed according to each age group. Results: Among all groups, MBTs (U12 r=.49- .55, U14 r=.52-.63, U16 r=.58-.60, U18 r=.51-.55; p<.05) as well as GS (U12 r=.43, U14 r=.57, U16 r=.59, U18 r=.59; p<.05) showed the highest correlations to service speed. Concerning anthropometric data, BW (U12 r=.47, U14 r=.55, U16 r=.57, U18 r= .44; p<.05) and AS (U12 r=.44, U14 r=.56, U16 r=.56, U18 r=.37; p<.05) were the most correlated showing moderate to large values. Results of multiple regression analysis indicated values of R² ranging from 41-66% concerning the explained variance of criterion variable (U12 R²= .41 (MBT OH+BH), U14 R²= .66 (MBT FH+OH, GS, AS), U16 R²= .62 (MBT OH+FH, GS), U18 R²= .46 (MBT FH, GS), p<.00). Discussion: Given a complex stroke as the tennis serve, results of regression as well as correlation analysis reinforce that service speed is strongly dependent on physical performance and anthropometric characteristics. Especially the upper body power/strength and the transfer of power from the lower to the upper body in proper timed sequences, which is needed in the MBT, highlight its importance for the junior player`s service while the purely lower body power (e.g. CMJ) seems to be less important. In this regard, intervention programs focusing on the specific requirements are recommended to increase serve performance.